Regioselective copper-catalyzed direct arylation of benzodithiophene-S, S-tetraoxide. Issue 37 (20th April 2017) - Khambhati, D. P.; Sachinthani, K. A. N.; Rheingold, A. L.; Nelson, T. L.
Abstract : An efficient copper-catalyzed direct arylation reaction for the regioselective functionalization of benzodithiophene- S, S -tetraoxide has been developed. Abstract : An efficient copper-catalyzed direct arylation reaction for the regioselective functionalization of benzodithiophene- S, S -tetraoxide has been developed. The method demonstrates a broad scope with isolated yields ranging from good to excellent. Furthermore, the reaction specificity for aryl iodides over the unreactive aryl bromides provide a opportunity to generate a new donor–acceptor–donor triad.